2019
DOI: 10.1093/sleep/zsz132
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous tonic and phasic REM sleep without atonia best predicts early phenoconversion to neurodegenerative disease in idiopathic REM sleep behavior disorder

Abstract: Study Objectives Rapid eye movement (REM) sleep without atonia (RWA) is the main polysomnographic feature of idiopathic REM sleep behavior disorder (iRBD) and is considered to be a promising biomarker predicting conversion to manifested synucleinopathy. Besides conventionally evaluated tonic, phasic and any RWA, we took into consideration also periods, when phasic and tonic RWA appeared simultaneously and we called this activity “mixed RWA.” The study aimed to evaluate different types of RWA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 36 publications
3
40
2
1
Order By: Relevance
“…Several other factors that are also linked to a prodromal state can improve the prediction of neurodegeneration. These include symptomatic orthostatic hypotension, olfactory dysfunction (by standardized testing), erectile dysfunction, hypersomnia, constipation, urinary dysfunction (typically urge incontinence), cognitive dysfunction, history of depression, diabetes, physical inactivity, and severity of RSWA [ 14 16 ]. Neuroimaging findings with predictive value include abnormal presynaptic tracer uptake (at least 2 standard deviations below the mean) on dopamine transporter SPECT or PET imaging and hyperechogenicity on ultrasound of the substantia nigra [ 17 ].…”
Section: Rem Sleep Behavior Disordermentioning
confidence: 99%
“…Several other factors that are also linked to a prodromal state can improve the prediction of neurodegeneration. These include symptomatic orthostatic hypotension, olfactory dysfunction (by standardized testing), erectile dysfunction, hypersomnia, constipation, urinary dysfunction (typically urge incontinence), cognitive dysfunction, history of depression, diabetes, physical inactivity, and severity of RSWA [ 14 16 ]. Neuroimaging findings with predictive value include abnormal presynaptic tracer uptake (at least 2 standard deviations below the mean) on dopamine transporter SPECT or PET imaging and hyperechogenicity on ultrasound of the substantia nigra [ 17 ].…”
Section: Rem Sleep Behavior Disordermentioning
confidence: 99%
“…13,16 Similarly, REM sleep without atonia has been identified as one of earliest signs of neurodegeneration 17,18 and a valuable prognostic biomarker of disease progression, as it increases over time and greater severity is associated with accelerated phenoconversion. 19,20 One study limitation is the small sample size. However, relying on our current results, chromatic pupillometry abnormalities might be proposed as a further potential early marker of parasympathetic affection and/or of mRGC dysfunction in iRBD.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] Consequently, recent studies indicated that RWA may serve as a biomarker for neurodegenerative disease emerged from iRBD. 46,47 To the best of our knowledge, this is the rst study that demonstrated the lower HMR may predict higher RWA. In this study, we set the cut-off value within the iRBD group and showed the association between decreased MIBG uptake and RWA.…”
Section: Discussionmentioning
confidence: 82%